Preliminary investigations on the viability of the use of abscisic acid (ABA) in crucifer seed health test for detecting Phoma lingam - Andreoli, Claudinei; Maguire, James D. (Pesquisa Agropecuaria Brasileira, 1995)
Phoma lingam, a seedborne fungal organism causes blackleg disease in crucifer (Brassicaceae). The recommended International Seed Testing Association (ISTA) procedure for determining the incidence of P. lingam in crucifer seed calls for examination of seed and blotters for typical pycnidia and conidial ooze, after 10-11 days of incubation at 20°C on blotters wetted with 0.2%, 2,4-D solution. The use of ABA at 100 mg/l is proposed as a new method for testing crucifer seed for P. lingam. The advantages of this seed assay are: a) ABA is totally soluble in water and using low concentration eliminates the risk of laboratory contamination; b) Seed pretreatment with sodium hypoclorite to reduce saprophytic contaminating fungi is not necessary; c) ABA is not toxic to P. lingam, thus it does not affect seed health testing, and d) ABA is available world wide and there is no difference in formulations. Suggestions have been made to the working group on seed-borne diseases of crucifer of the ISTA Plant Disease Commitee to compare this method with the presently recommended 2,4-D test.